The effect of a concentrated period of soccer-specific fitness training with small-sided games on physical fitness in youth players - Paul, D. J.; Marques, J. B.; Nassis, G. P. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: It is unknown whether a concentrated period of small-sided games and high intensity training is an effective training approach in youth soccer players. The aim of the study was to examine the effect of a concentrated period of soccer specific training on physical fitness in youth players. METHODS: Nineteen male soccer players, from two teams, participated (mean age: 16.2±0.8 years; body mass: 58.2±7.6 kg; height: 170.8±7.7 cm). One team performed 5 days of small-sided games and high intensity training (SSG & HIT; N.=12) and the other team regular soccer training with 1 day of SSG and HIT (REG; N.=7) weekly for 4 weeks. The 30-15 intermittent fitness test (30-15 IFT), countermovement jump (CMJ) and change of direction (COD) performance were measured pre and post intervention. Heart rate (HR) and rating of perceived exertion (RPE) were recorded and session load calculated (RPE x minutes). RESULTS: Average percentage of maximum HR and session load were 83% and 344 AU for the SSG & HIT versus 73% and 253 AU for the REG (P<0.05). 30-15 IFT improved for the SSG & HIT (from 17.0±1.1 to 18.4±0.8 km/h; P<0.05; ES=0.57) with no difference for the REG group (Pre: 17.9±1.3, Post: 18.2±1.6 km/h, ES=0.10). CMJ and COD were unchanged in both groups and no injuries were reported. CONCLUSIONS: A 4-week concentrated period of daily SSG & HIT is effective for improving endurance performance in youth soccer players. This was without injuries and without negating performance in power and change of direction.